Pengaruh Literasi Ekonomi, Media Iklan, dan Kontrol Diri Terhadap Perilaku Pembelian Impulsif pada Generasi Z di Kota Makassar - Alifka Alya Zhafirah; Hasan, Muhammad; Inanna; Ratna; Judijanto, Loso (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
This research aims to find out how economic literacy, advertising media, and self-control of generation Z in Makassar relate to impulsive buying behavior. In this research, quantitative and descriptive methods were used. This research focuses on the demographics of generation Z, namely Makassar people born between 1996 and 2009. Nonprobability sampling and incidental sampling methods were used in the sampling strategy. Data collection methods used include observation, surveys, and writing information. The SPSS application uses several data analysis techniques, including multiple linear regression analysis, t test, and f test. Research findings show that in Makassar City, Generation Z (Y)'s impulse buying behavior is influenced by economic literacy (X1), advertising media (X2), and self-control (X3).